Multi-pollutant assessment of river pollution from livestock production worldwide. (1st February 2022) - Li, Yanan; Wang, Mengru; Chen, Xuanjing; Cui, Shilei; Hofstra, Nynke; Kroeze, Carolien; Ma, Lin; Xu, Wen; Zhang, Qi; Zhang, Fusuo; Strokal, Maryna
Highlights: Our global multi-pollutant model quantifies pollution from livestock to rivers. Over 57% of nutrients and oocysts on land are from grazed animal systems. Asia, south america and africa contribute by 68% to nutrients and oocysts on land. Cattle, pigs and chickens are responsible for 74–88% of nutrients and oocysts in rivers. One-fourth of global sub-basin areas contribute by 71–95% to river pollution. Abstract: Livestock production is often a source of multiple pollutants in rivers. However, current assessments of water pollution seldomly take a multi-pollutant perspective, while this is essential for improving water quality. This study quantifies inputs of multiple pollutants to rivers from livestock production worldwide, by animal types and spatially explicit. We focus on nitrogen (N), phosphorus (P), and Cryptosporidium (pathogen). We developed the MARINA-Global-L (M odel to A ssess R iver I nputs of pollutaN ts to seA s for L ivetsock) model for 10, 226 sub-basins and eleven livestock species. Global inputs to land from livestock are around 94 Tg N, 19 Tg P, and 2.9 × 10 21 oocysts from Cryptosporidium in 2010. Over 57% of these amounts are from grazed animals. Asia, South America, and Africa account for over 68% of these amounts on land. The inputs to rivers are around 22 Tg Total Dissolved Nitrogen (TDN), 1.8 Tg Total Dissolved P (TDP), and 1.3 × 10 21 oocysts in 2010. Cattle, pigs, and chickens are responsible for 74–88% of these pollutants in rivers. One-fourth of the global sub-basins can be considered pollution hotspots and contribute 71–95% to the TDN, TDP, and oocysts in rivers. Our study could contribute to effective manure management for individual livestock species in sub-basins to reduce multiple pollutants in rivers. Graphical abstract: Image, graphical abstract